On the frequency and voltage dependence of admittance characteristics of Al/PTCDA/P-Si (MPS) type Schottky barrier diodes (SBDs) - Tecimer, H.; Uslu, H.; Alahmed, Z. A.; Yakuphanoğlu, Fahrettin; Altindal, S. (Elsevier Sci Ltd, 2014)
The admittance measurements which are including capacitance/conductance-voltage-frequency (C-V-f and G/omega-V-f) measurements of the Al/PTCDA/p-Si (MPS) type Schottky barrier diodes (SBDs) were investigated in the frequency and voltage range of 10 kHz-1 MHz and (-3 V) to (3 V) at room temperature. C and G/omega values were found as strong functions of frequency especially in depletion and accumulation regions due to the effect of interface states (N-ss) and series resistance (R-s), respectively. The main electrical parameters such as doping concentration atoms (N-A), diffusion potential (V-d), Fermi energy level (E-F) and barrier height (Phi(B)(C-V)) values were obtained from the reverse bias C-2 VS V plots for each frequency. The voltage dependent resistivity (R-i) profile was also obtained from the C-i and G(i) data and they exhibit an anomalous peak in the depletion region due to particular distribution of N-ss at polymer (PTCDA)/Si interface. In addition, the energy density distribution profile of N-ss and their relaxation time (tau) were obtained from the measured C-f and G/omega similar to f characteristics for various forward bias voltages and they were ranged from 3.06 x 10(12) eV(-1) cm(-2) to 3.29 x 10(12) eV(-1) cm(-2) and 6.20 mu s to 8.41 mu s, respectively, in the energy range of E-v-0.479 and E-v-0.501 eV, respectively. These results confirmed that the value of N-ss may be passivized by PTCDA interfacial layer and such low value of N-ss is very suitable for the fabrication MPS type SBDs in the electronic industry. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Thin films; Electrical properties; Interface/interphase